Business Law I Essentials - Valbrune, Mirande; De Assis, Renee; Cardell, Suzanne (Open textbook library., 2019)
Business Law I Essentials is a brief introductory textbook designed to meet the scope and sequence requirements of courses on Business Law or the Legal Environment of Business. The concepts are presented in a streamlined manner, and cover the key concepts necessary to establish a strong foundation in the subject. The textbook follows a traditional approach to the study of business law. Each chapter contains learning objectives, explanatory narrative and concepts, references for further reading, and end-of-chapter questions. Business Law I Essentials may need to be supplemented with additional content, cases, or related materials, and is offered as a foundational resource that focuses on the baseline concepts, issues, and approaches.